2015
DOI: 10.3389/fpls.2015.00335
|View full text |Cite
|
Sign up to set email alerts
|

Comparative conventional- and quantum dot-labeling strategies for LPS binding site detection in Arabidopsis thaliana mesophyll protoplasts

Abstract: Lipopolysaccharide (LPS) from Gram-negative bacteria is recognized as a microbe-associated molecular pattern (MAMP) and not only induces an innate immune response in plants, but also stimulates the development of characteristic defense responses. However, identification and characterization of a cell surface LPS-receptor/binding site, as described in mammals, remains elusive in plants. As an amphiphilic, macromolecular lipoglycan, intact LPS potentially contains three MAMP-active regions, represented by the O-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 72 publications
0
3
0
1
Order By: Relevance
“…Our previous work has shown that LPS from B. cepacia initiate characteristic MAMP responses typically mediated by pattern‐recognition receptors (PRRs) in plants . Nt‐Sd‐RLK was first identified as a differentially expressed, LPS‐responsive transcript .…”
Section: Resultsmentioning
confidence: 99%
“…Our previous work has shown that LPS from B. cepacia initiate characteristic MAMP responses typically mediated by pattern‐recognition receptors (PRRs) in plants . Nt‐Sd‐RLK was first identified as a differentially expressed, LPS‐responsive transcript .…”
Section: Resultsmentioning
confidence: 99%
“…Both light chains (CLCs) and clathrin heavy chains (CHCs), including CHC1 and CLC3, were identified in the non-enriched PM-associated fraction (Table 1 and Table 2). In this regard, Mgcina et al [41] also speculated that the binding-site of lipopolysaccharide (LPS) as a bacterial MAMP to A. thaliana protoplasts is internalized into the cell by endocytosis, thus leading to the reduced level of receptors on the surface.…”
Section: Discussionmentioning
confidence: 99%
“…SA regulates endocytosis by interfering with clathrin-mediated protein trafficking but did not affect flg22-induced endocytosis of the FLS2 receptor during pathogen responses in Arabidopsis [143]. Mgcina et al [144] proposed that LPS binding might involve ligandinduced receptor endocytosis and recycling in Arabidopsis. Endocytosis of PM-localised PRR for recycling or degradation involving transport and trafficking proteins is part of the regulation of ligand-induced defence signalling [63,121].…”
Section: Pm-associated Proteins Related To Membrane Transport and Tra...mentioning
confidence: 99%